Time of the day and season distribution among stroke code subtypes: differences between ischemic stroke, intracranial hemorrhage, and stroke mimic - Menéndez Albarracín, Alex; Valls Carbó, Adrián; Rabaneda Lombarte, Neus; Yugueros Baena, Bárbara; Carbonell Gisbert, Jaime; Flores-Pina, Belén; Larrañaga De Bofarull, Maria-Clara; Martínez Sánchez, Marina; Hernández-Pérez, María; Bustamante Rangel, Alejandro; Dorado Bouix, Laura; Gomis Cortina, Meritxell; et al. (Frontiers in Neurology, 2024)
Background Circadian variations in the timing of the onset of stroke symptoms have been described, showing a morning excess of cardiovascular risk. To date, no differences have been found between stroke subtype and time distribution throughout the day. The present study aims to compare the seasonal and circadian rhythm of symptoms onset in ischemic, hemorrhagic, and stroke mimic patients. Methods This study was conducted prospectively at a hospital and involved a cohort of stroke alert patients from 2018 to 2021. Stroke subtypes were classified as ischemic stroke, intracerebral hemorrhage (ICH), transient ischemic attack (TIA), and stroke mimic. Clinical variables were recorded, and each patient was assigned to a 4-h interval of the day according to the time of onset of symptoms; unwitnessed stroke patients were analyzed separately. Seasonal changes in stroke distribution were analyzed at 3-month intervals. Results A total of 2,348 patients were included in this analysis (ischemic 67%, ICH 13%, mimic 16%, and TIA 3%). Regardless of stroke subtype, most of the patients were distributed between 08–12 h and 12–16 h. Significant differences were found in the time distribution depending on stroke subtype, with ICH predominating in the 4–8 h period (dawn), most of which were hypertensive, TIA in the 12–16 h period (afternoon), and stroke mimic in the 20 h period (evening). The ischemic stroke was evenly distributed throughout the different periods of the day. There were no differences in the seasonal pattern between different stroke subtypes, with winter being the one that accumulated the most cases. Conclusion The present study showed different circadian patterns of stroke subtypes, with a predominance of ICH at dawn and stroke mimic in the afternoon. The stroke circadian rhythm resembles previous studies, with a higher incidence in the morning and a second peak in the afternoon.